Implementasi Tingkat Kesehatan Kinerja Keuangan Dan Potensi Financial Distress Melalui Pendekatan RGEC Dan ZMIJEWSKI Pada Bank Muamalat Indonesia Periode 2017-2021 - Lola Triaulina; Muhammad Iqbal Surya Pratikto (Al-Muraqabah: Journal of Management and Sharia Business, 2023)
The role of banking in running the wheels of the economy is very complex, so that banking institutions become one of the bodies that contribute to maintaining and maintaining the stability of the country's economy. One of the methods used to determine the soundness of banking is RGEC which has four components, including Risk Profile, Good Corporate Governance, Earnings, Capital. This research was conducted with the aim of knowing the soundness level of Bank Muamalat Indonesia during the last 2017 to 2021 period. The type of research used is the explanatory research method with the RGEC approach. The data source used is secondary data obtained from the website of Bank Muamalat Indonesia which contains financial reports for the period listed. The results of this study can be presented in the form of graphs and tables to make it easier to analyze. So the final results obtained for the period 2017 to 2021 are that Bank Muamalat Indonesia is in the third rank category or is at the soundness level with the "fairly healthy" category. This is in line with the results of research on the level of bankruptcy of Bank Muamalat Indonesia during the 2017-2021 period which received the title of "fairly healthy" in the last four periods, even though in 2017 it had experienced a high risk of bankruptcy.